EP054/#637 Patterns of use of primary chemotherapy and first-line chemotherapy for recurrence among patients with cervical cancer. (4th December 2022) - Diggs, Alexandra; Huang, Yongmei; Melamed, Alexander; Szamreta, Elizabeth; Monberg, Matthew; Wright, Jason
Abstract : Objectives: Little is known about the patterns of chemotherapy use in women with cervical cancer. We examined chemotherapy use in the primary setting and at the time of first recurrence Methods: We identified patients in the IBM MarketScan database with cervical cancer who underwent first-line hysterectomy or radiation therapy between 2011–2020. The use of clinically relevant therapeutic regimens was determined in the primary setting and at the time of first recurrence Results: We identified a total of 5390 patients: 2667 (49.5%) underwent primary hysterectomy and 2723 (50.5%) received primary radiotherapy. Among patients who underwent primary hysterectomy, 36.7% received adjuvant radiation, and 23.1% received primary chemotherapy. The most common chemotherapy regimens were single agent platinum (51.7%), platinum combination therapy (35.2%) and non-platinum drugs (3.4%). Among patients treated with primary radiation, 73.6% received primary/concurrent chemotherapy, either platinum alone (66.4%), platinum in combination with another agent (32.2%), or non-platinum drugs (1.4%). The median duration of primary chemotherapy was 1.2 months. Therapy for recurrent cervical cancer was initiated in 959 patients. The most commonly used regimens were platinum combination (63.9%), non-platinum cytotoxic agents (16.5%), single platinum agent (14.9%), targeted therapy with bevacizumab (6.0%) and immunotherapy with pembrolizumab (3.2%). The median duration of first-line chemotherapy for recurrence was 2.5 months (IQR, 1.2–5.1 months). Conclusions: Platinum-based chemotherapy is the most commonly used therapy in patients with cervical cancer in the primary setting and at the time of recurrence. The rate of utilization of non-platinum agents at first recurrence has increased over time.